(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article analyzes the influence of the native language on learning English as a foreign language. It examines the main aspects of language interference, its positive and negative aspects, and how it manifests itself in Uzbek-speaking and Russian-speaking students. Particular attention is paid to methodological approaches aimed at minimizing errors and improving learning effectiveness.